2011
DOI: 10.1002/jcb.23234
|View full text |Cite
|
Sign up to set email alerts
|

BMI1 as a novel target for drug discovery in cancer

Abstract: Growing evidence has demonstrated that clonogenic cancer stem (initiating) cells are responsible for tumor regrowth and disease relapse. Bmi-1 plays a critical role in the self-renewal of adult stem cells. The Bmi-1 protein is elevated in many types of cancers, and experimental reduction of Bmi-1 protein levels by small interfering RNA (siRNA) causes apoptosis and/or senescence in tumor cells in vitro and increases susceptibility to cytotoxic agents. The Bmi-1 protein has no known enzymatic activity, but serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 81 publications
8
152
0
Order By: Relevance
“…BMI-1 is a member of a family of transcriptional repressors [15] and a known upstream modulator of p16 [16]. BMI-1's effect on p16 expression is of interest as p16 is widely in clinical use as a surrogate marker of HPV infection in OPSCC [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI-1 is a member of a family of transcriptional repressors [15] and a known upstream modulator of p16 [16]. BMI-1's effect on p16 expression is of interest as p16 is widely in clinical use as a surrogate marker of HPV infection in OPSCC [3].…”
Section: Discussionmentioning
confidence: 99%
“…This contradiction could be explained by the fact that, in addition to its repressive effect on tumor suppressor p16, BMI-1 acts also via numerous other pathways independent of p16. It has also been suggested that BMI-1 alone should not be sufficient for tumor progression [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…While debate continues as to the precise identity and function of CSCs, there is common agreement that CSCs show increased chemoresistance and radioresistance. (140)(141)(142)145) Therefore, understanding the biology of chemoresistance potential of CSCs may contribute to our understanding of tumor biology and would have far-reaching clinical implications.…”
Section: Csc Conceptmentioning
confidence: 99%
“…(146) BMI1 is reported to play a crucial role in self-renewal of stem cells and is associated with a number of human malignancies. (141,144,(147)(148)(149) Recent studies suggest that BMI1 is involved in the initiation of cancer, and targeting BMI1 by gene therapy abolishes chemoresistance in tumor cells. (141,142) The inability of tumor cells to go through apoptosis in response to chemotherapy gives a selective advantage for tumor progression, metastasis, and resistance to therapy.…”
Section: Csc Conceptmentioning
confidence: 99%
“…It is uniquely expressed by the rapidly cycling stem cells, but is dispensable for Lgr5 stem cell self-renewal and differentiation [24]. Bmi1 is a member of the Polycomb Repressive Complex 1 (PRC1); it is expressed in stem cells in several tissues [25] and within the gut it is expressed in the quiescent +4 stem cells.…”
Section: Gene Expression Signatures Of Intestinal Stem Cells Bulk Upmentioning
confidence: 99%